(3CfHGA CHfGA GdRef aj JGQjN Gdjefs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdoenDnqjO HGddg,J (B745 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdJGQjN deG cGf eYQaJg ef LedI GdYdhe GdOjfjg haf GdahGjO s
(3BNQgG (B:s
(3hOaf HGdbHI GdJi CfTCgG HGdCHgQ s
(3LeYg GdeDda ef fMh SHYI hNeSjf JGQjNkG hQnqJHg Ydi GdSfjf hhUd ajg Edi SfI (B1046s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B143 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B195s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B1347) s
Keywords: (3GdJGQjNs